Pengembangan Media Pembelajaran Teks Eksplanasi Berbantuan Aplikasi VN untuk Meningkatkan HOTS Siswa Kelas XI di Mas Proyek Univa Medan - Sakinah, Nurul; Ali, Ali; Kartika, Rika (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2024)
This study aimed to develop and assess the feasibility of learning media assisted by the VN application for identifying information in explanatory texts in class XI MIPA-1 MAS at Univa Project Medan, based on evaluations from media and material experts. The student population included classes XI MIPA-1, XI MIPA-2, and XI IIS, with data collected through questionnaires and interviews. Utilizing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the research indicated that the VN application-based learning media effectively facilitated information identification in the explanatory texts, meeting feasibility criteria. Media experts rated the validity at 94%, while material experts rated it at 86%. Teachers' evaluation averaged at 92%, and students responded positively with an average score of 93%. In conclusion, the VN application-supported learning media for identifying information in explanatory texts is valid and suitable for classroom use in class XI MIPA-1 MAS at Univa Project Medan.